2020
DOI: 10.1507/endocrj.ej19-0610
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin levels by ECLIA correlate well with RIA values in higher range but are affected by sex, TgAb, and renal function in lower range

Abstract: Calcitonin (CT) is a marker for both initial diagnosis and monitoring of patients with residual or recurrent medullary thyroid carcinoma (MTC). In Japan, serum CT had been measured by radioimmunoassay (RIA) until recently. Electrochemiluminescence immunoassay (ECLIA) became commercially available in 2014, and this technique is now the only method used to examine CT concentration. The purposes of this study were to investigate the correlations between the CT concentration measured with ECLIA (ECLIA-CT) and RIA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although we did not directly compare ELFA and ECLI, the differences between ELFA and RIA were more moderate than between RIA and ECLI. In another species such as human, some kinds of hormonal levels are detected at a higher range in the ECLI system than in the ELFA system, as well as in the ELFA system than in the RIA system [31][32][33], indicating that the sensitivity of the systems has improved over time. In this study, considering the standard curve of P4 based on range and estrus day, a P4 range of 4.0-8.0 ng/mL based on RIA that corresponded to the ovulation day was measured at 5.0-12.0 ng/mL using ELFA.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not directly compare ELFA and ECLI, the differences between ELFA and RIA were more moderate than between RIA and ECLI. In another species such as human, some kinds of hormonal levels are detected at a higher range in the ECLI system than in the ELFA system, as well as in the ELFA system than in the RIA system [31][32][33], indicating that the sensitivity of the systems has improved over time. In this study, considering the standard curve of P4 based on range and estrus day, a P4 range of 4.0-8.0 ng/mL based on RIA that corresponded to the ovulation day was measured at 5.0-12.0 ng/mL using ELFA.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported the presence of CCH in some thyroid specimens with Hashimoto’s thyroiditis [19], while others reported decreased serum CT values probably caused by atrophy, fibrosis, and destruction of both follicular and C-cells [15]. Recently, Ito et al [23] found a significant association between ECLIA-CT and TgAb titer: ECLIA-CTs were statistically lower in the TgAb positive group than in the TgAb negative group suggesting that CT level might be affected by thyroiditis.…”
Section: Discussionmentioning
confidence: 99%